2009
DOI: 10.1111/j.1442-8903.2009.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Does diversity influence soil nitrate, light availability and productivity in the establishment phase of Australian temperate grassland reconstruction?

Abstract: This research arose from the need to progress the use of direct seeding in the restoration of species-rich temperate Australian grassland.Summary The successful conservation and restoration of the temperate native grasslands of south-eastern Australia is critical to reversing the decline in range and diversity of these threatened plant communities. Yet the goals of high native species diversity and weed management are difficult to achieve in grassland restoration projects. To increase our understanding of whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…plains grassland, plains grassy woodland, grassy dry forest) and to identify regional seed collection sites. Gibson‐Roy et al. (2009) found that high levels of plant diversity (species and functional) could be established early in the grassland restoration cycle.…”
Section: A General Overview Of the Ggrp Programmementioning
confidence: 99%
“…plains grassland, plains grassy woodland, grassy dry forest) and to identify regional seed collection sites. Gibson‐Roy et al. (2009) found that high levels of plant diversity (species and functional) could be established early in the grassland restoration cycle.…”
Section: A General Overview Of the Ggrp Programmementioning
confidence: 99%
“…The establishment time for the C4 species in our study may not have been sufficient to make them successful competitors. Another southern Australian study (but with higher average rainfall, particularly in summer), found that T. triandra, the dominant C4 species in our study, took longer than other species to become established (Gibson-Roy et al, 2009). We attempted to overcome this delay by planting mature tubestock plants rather than using direct seeding.…”
Section: C4 Native Plants Were Not Strong Competitorsmentioning
confidence: 89%
“…For example in box gum woodlands, increased species diversity during the early phase of restoration has been associated with reduced soil nitrate concentrations, suggesting greater resistance to exotic annual invasion during this critical phase (Gibson‐Roy et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, processes associated with both resistance and resilience have been attributed to various elements of species composition within an ecosystem. For example in box gum woodlands, increased species diversity during the early phase of restoration has been associated with reduced soil nitrate concentrations, suggesting greater resistance to exotic annual invasion during this critical phase (Gibson-Roy et al 2009). Fargione & Tilman 2005;Prober et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation